Green Infrastructure and Regional Planning: An Operational Framework An Operational Framework - Isola, Federica (Territorio sostenibilità governance, 2022)
Identifying and planning green infrastructures at the regional scale can be considered an intentional way of spreading the positive impacts of environmental conservation policies across spatial contexts much more complex and larger than protected areas. In this volume, a methodological approach is defined and experimentally implemented into the Sardinian region (Italy), in order to identify both a regional green infrastructure, and a network of ecological corridors, conceived as edges connecting the regional protected areas. This approach supports spatial decision-making processes aimed at addressing environmental hazards connected to landslides and floods, as well as at establishing effective spatial planning rules.